Design of a wide bandwidth and high efficiency circularly polarized microstrip patch antenna using coaxial feeding technique. Issue 4 (8th March 2018) - Hossain, Sheikh Dobir; Rita,; Sobahan, K. M. Abdus; Mallick, Rony; Hossain, F.
Abstract: A single band circularly polarized rectangular microstrip patch antenna has been simulated from the cavity equation at first and then the antenna design has been extended to 2 × 2 array. The length and thickness of the each element of the rectangular patch antenna with a slot in the center of the rectangular patch are 38 mm and 0.1 mm, respectively, which are comparatively smaller than our previously presented single‐element circularly polarized microstrip antenna with an I‐slot. In comparison to the bandwidth and efficiency of single element antenna, the quantity have increased about 39% and more than 90%, respectively, in the desired array antenna at the same resonant frequency that is 2.8 GHz. In this article, we also have studied and presented the return loss, bandwidth, gain, directivity, axial ratio of our aimed antenna.